Analysis Problem Solving Errors in Mathematics Story Questions - Era Setiyawati; Endang Fauziati; Darsinah; Minsih; Yenny Prastiwi (Jurnal Pendidikan Indonesia, 2022)
Daily problems are often expressed in the form of math story problems. However, mathematics is often seen as scary because it is difficult to learn, causing errors in doing math story problems. The aims of this study is analyses the types of problem-solving errors in solving math story problems and analyses the factors that cause problem solving errors in solving math story problems. This research is a type of qualitative research with a case study approach. The subjects in this study were elementary school students in grade 5 with the object of research being student errors in answering math story questions. Data collection techniques using question answer sheets and interviews. The data analysis technique uses Miles and Huberman interactive data analysis techniques. The results showed that reading errors were 39%, comprehension errors were 81%, transformation errors were 88%, process skill errors as much as 90%, and writing errors in the final answer (encoding errors) as much as 90%. Cognitive factors that cause problem solving errors in math story problems are: memory weakness; the weakness of understanding; and weak analysis. The non-cognitive factors that cause problem-solving errors in math story problems are how students learn and how to teach teachers. Based on the results of the study, teachers need to improve students' abilities to reduce process skill errors and writing errors in the final answer.